2011
DOI: 10.1021/es203512t
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon in Antarctic Snow: Spatial Trends and Possible Sources

Abstract: Organic carbon records in Antarctic snow are sparse despite the fact that it is of great significance to global carbon dynamics, snow photochemistry, and air-snow exchange processes. Here, surface snow total organic carbon (TOC) along with sea-salt Na(+), dust, and microbial load of two geographically distinct traverses in East Antarctica are presented, viz. Princess Elizabeth Land (PEL, coast to 180 km inland, Indian Ocean sector) and Dronning Maud Land (DML, ∼110-300 km inland, Atlantic Ocean sector). TOC ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…It is known that organic compounds deposited on glaciers will experience a series of depletion processes and photochemical reactions (Grannas et al, 2004;Antony et al, 2011;Niu et al, 2017b). Depletion process of WSOC in surface aged snow was investigated based on successive insitu observations, the results indicated that WSOC concentrations were dramatically decreased with the time extension during the entire monsoon season (Fig.…”
Section: Depletion and Leaching Of Wsoc In The Snowpackmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that organic compounds deposited on glaciers will experience a series of depletion processes and photochemical reactions (Grannas et al, 2004;Antony et al, 2011;Niu et al, 2017b). Depletion process of WSOC in surface aged snow was investigated based on successive insitu observations, the results indicated that WSOC concentrations were dramatically decreased with the time extension during the entire monsoon season (Fig.…”
Section: Depletion and Leaching Of Wsoc In The Snowpackmentioning
confidence: 99%
“…Glacier ecosystem accumulates OC from in-situ primary production as well as from the deposition of impurities derived from anthropogenic and natural sources (Singer et al, 2012;Stibal et al, 2012). OC records in glaciers are of great significance to global carbon dynamics, snow photochemistry, and air-snow exchange processes (Antony et al, 2011;Niu et al, 2017a). It was also known that photochemical reactions of OC in snow and ice can release reactive gaseous species into the overlying atmosphere (Guimbaud et al, 2002;Grannas et al, 2004;Niu et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported DOC concentration in rainwater varies over five orders of magnitude, from 60 to 204,000 μg-C/L. The concentration of DOC in ice and snow is typically lower than in rainwater; for instance, the measured concentration in Antarctic snow ranged from 88 to 928 μg-C/L (Antony et al 2011) and in ice cores ranged from 2 to 100 μg-C/L (Preunkert et al 2011).…”
Section: Introductionmentioning
confidence: 99%